Perception of Primary School Teachers towards the Implementation of Project Based Learning - Cintang, Nyai; Setyowati, Dewi Liesnoor; Dewanti Handayani, Sri Sularti (Universitas Negeri Semarang, 2017)
The research focuses to study the perception of primary school teacher on project based learning. The teacher's perception of project based learning is related to the way the teacher designs and implements project based learning. This research aims to: (1) assess the teacher's perception on the implementation of project based learning in primary school, and (2) to study how the teacher interprets project based learning in the implementation. The result of this research shows that: (1) every teacher has a different perception on the implementation of project based learning. Teacher's perception is seen from the understanding of meaning, role of the teacher, role of the student, the required components to be prepared, the urgency and the advantages, as well as the assessment used by the teacher. (2) The teacher's perception on the implementation of project based learning is closely related to the way the teacher interprets project based learning. The interpretation of project based learning in terms of its implementation, use of guidance, defining problem, defining project, and the context of implementation. Based on the results, it can be concluded that teacher's perception on the implementation of project based learning in primary school has special characteristics which derive different interpretations of project based learning conducted in the pilot project primary school.